2013
DOI: 10.1007/s10008-013-2215-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anode surface area on nanoporous oxide formation during anodizing of low purity aluminum (AA1050 alloy)

Abstract: Porous anodic alumina layers were obtained by a simple two-step anodization of low purity aluminum (99.5 % Al, AA1050 alloy) in a 0.3 M oxalic acid electrolyte at 45 V and 20°C. The effect of anode surface area on structural features of nanoporous oxide and process of oxide formation was investigated. An ordered structure composed of nanostripes or nanopores was formed on the Al surface during electrochemical polishing in a mixture of perchloric acid and ethanol. This nanopattern is then replicated during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…During prolonged anodization of as pre-textured aluminum the lowest resistance and the highest electric field are observed at the bottom of each concave. Hence, the pore nucleation occurs easier, so the lower rate of the barrier oxide growth and more rapid increase in current density are observed [36]. This dependence observed in our group for AA1050 is in excellent agreement with the results obtained e.g., by Li et al [50], and Wang et al [51] for anodization of high-purity substrates.…”
Section: Anodic Alumina Growthsupporting
confidence: 89%
See 2 more Smart Citations
“…During prolonged anodization of as pre-textured aluminum the lowest resistance and the highest electric field are observed at the bottom of each concave. Hence, the pore nucleation occurs easier, so the lower rate of the barrier oxide growth and more rapid increase in current density are observed [36]. This dependence observed in our group for AA1050 is in excellent agreement with the results obtained e.g., by Li et al [50], and Wang et al [51] for anodization of high-purity substrates.…”
Section: Anodic Alumina Growthsupporting
confidence: 89%
“…We also confirmed that the pattern formed on the Al surface by electropolishing is then replicated at the initial stages of first anodizing step (compare Fig. 3.3c, d), so the morphology of initial nanoporous oxide is strongly determined by the morphology of aluminum substrate used as a starting material for anodization [36]. It was also reported that the significant improvement of nanostructured oxide morphology can be also achieved by annealing of impure Al foils prior to anodizing that could be attributed to the reduction of amount of grain boundaries and smoothing of the Al surface during annealing [40].…”
Section: Al Substrate Pre-treatmentsupporting
confidence: 82%
See 1 more Smart Citation
“…at the constant potential of 20 V and 0 8C for 30 s. The porous anodic aluminum oxide (AAO) films were prepared by a two-step anodization under the constant cell voltage of 45 V in 0.3 M H 2 C 2 O 4 at 25 8C, as described previously [23][24][25][26][27]. The duration of the first and second anodizing steps was 1 h and 5 h, respectively.…”
Section: Fabrication Of Nanoporous Aao Templatesmentioning
confidence: 99%
“…She introduced the Tafel equation and the concept of chemical potential, as well as a view of APA cell nucleation based on flakes of oxides. The comprehensive picture given by Dr. Runge may help to understand metallurgical issues [19] and side effects emerging during APA fabrication from Al alloys [20], which in the future could foster the use of recycled Al from e.g. beverage cans or food packaging.…”
Section: Volume 1 | Issuementioning
confidence: 99%